Hepatoprotective Effect of Cereal Vinegar Sediment in Acute Liver Injury Mice and Its Influence on Gut Microbiota - Guan, Qijie; Gong, Tingting; Lu, Zhen-Ming; Geng, Yan; Duan, Wenhui; Ren, Yi-Lin; Zhang, Xiao-Juan; Chai, Li-Juan; Shi, Jin-Song; Xu, Zheng-Hong (Frontiers in Nutrition, 2021)
Cereal vinegar sediment (CVS) is a natural precipitate formed during the aging process of traditional grain vinegar. It has been used as Chinese traditional medicine, while its composition and function are reported minimally. In this study, we measured CVS in terms of saccharide, protein, fat and water content, and polyphenol and flavonoid content. Furthermore, we determined the amino acids, organic acids, and other soluble metabolites in CVS using reverse-phase high-performance liquid chromatography (RP-HPLC), HPLC, and liquid chromatography with tandem mass spectrometry (LC-MS/MS) platforms. The hepatoprotective effect of CVS was evaluated in acute CCl4-induced liver injury mice. Administration of CVS for 7 days prior to the CCl4 treatment can significantly decrease liver alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels and reactive oxygen species (ROS) levels, compared with those in the hepatic injury model group. The gut microbiota was changed by CCl4 administration and was partly shifted by the pretreatment of CVS, particularly the Muribaculaceae family, which was increased in CVS-treated groups compared with that in the CCl4 administration group. Moreover, the abundances of Alistipes genus and Muribaculaceae family were correlated with the liver ALT, AST, and malondialdehyde (MDA) levels. Our results illustrated the composition of CVS and its hepatoprotective effect in mice, suggested that CVS could be developed as functional food to prevent acute liver injury.